Influence of Social Workers' Empathy Ability on Suicidal Ideation of Cancer Patients - Yang, Ningxi; Zhang, Yuting; Liu, Zhibo; Wang, Fang; Yang, Guoqing; Hu, Xiuying (Frontiers in Public Health, 2022)
Background The nursing goal of patients with cancer is to provide them with holistic care, including physical, psychological, and social adaptation, and spirituality. This research aimed to explore the influence of the social workers' empathy ability on suicidal ideation of patients with cancer and its path. Methods There was a sum of 358 patients with cancer and the 45 social workers serving them participated in the survey. Data of their self-efficacy, depression symptom, stigma, and suicidal ideation were measured before the social work provided (T1) and 3 months after the social work finished (T2) were collected and compared. Pearson correlation analysis was used to assess the relationships between social workers' empathy ability and patient indicators at T2. The influence path of social workers' empathy ability on cancer patients' suicidal ideation was explored by path analysis at T2. Results At T2, patients reported higher self-efficacy and lower depression symptoms, stigma, and suicidal ideation than at T1. At T2, social workers' empathy ability was positively related to patients' self-efficacy and was negatively related to depression symptoms, stigma, and suicidal ideation. Social workers' empathy ability affected patients' suicidal ideation directly. In addition, patients' self-efficacy, depression symptoms, and stigma played mediating roles in the influence of social workers' empathy abilities on their suicidal ideation. Conclusion Social workers' empathy ability not only directly affected cancer patients' suicide ideation but also affected suicide ideation through the mediating roles of self-efficacy, depression symptoms, and stigma. Therefore, the improvement of the empathy ability of medical social workers needs to be paid attention to.